Dynamic human capital management in Malaysian public sector organisation - Abd Rahman, Hairulniza; Mohd Khushairi, Noor Azreen; Kamaruddin, Kardina; Omar, Siti Nur Zahirah; Mohamad, Mutiiah (International Journal of Accounting, Finance and Business, 2025)
This study investigates the dynamics of human capital management (HCM) within Malaysian public sector organisations, emphasizing its critical role in knowledge transfer behaviour (KTB). As the public sector faces increasing challenges, effective HCM strategies are essential for sustaining knowledge flow and enhancing organisational performance. Utilizing a sample of 173 employees from various levels within the Malaysian public sector employees, the research employs WarpPLS software and PLSSEM analysis to explore the relationship between HCM and KTB. The findings reveal a significant positive correlation, with a beta value of 0.28 and an R-squared value of 0.210, indicating that enhanced human capital positively influences knowledge transfer behaviour. The results support hypothesis, confirming that as human capital value increases, so does the effectiveness of knowledge transfer among employees. This study underscores the importance of fostering an inclusive organisational culture that leverages generational creativity to optimize human capital resources, ultimately improving public sector performance in Malaysia.